Mutations in an Atypical TIR-NB-LRR-LIM Resistance Protein Confer Autoimmunity - Bi, Dongling; Johnson, Kaeli; Huang, Yan; Zhu, Zhaohai; Li, Xin; Zhang, Yuelin (Frontiers in Plant Science, 2011)
In order to defend against infection, plants employ a complex immune system that relies partly on resistance (R) proteins which initiate intricate signalling cascades upon pathogen detection. The resistance signalling network in plants is only partially characterized. A genetic screen conducted to identify novel defense regulators involved in this network resulted in the isolation of the snc6-1D mutant. Positional cloning revealed that this mutant contained a molecular lesion in the CHILLING SENSITIVE 3 (CHS3) gene, thus the allele was renamed chs3-2D. CHS3 encodes a TIR-NB-LRR R protein that contains a C-terminal zinc-binding LIM (Lin-11, Isl-1, Mec-3) domain. Although this protein has been previously implicated in cold stress and defense response, the role of the LIM domain in modulating protein activity is unclear. The chs3-2D allele contains a G to A point mutation causing a C1340 to Y1340 substitution close to the LIM domain. It encodes a dominant, gain-of-function mutation. The chs3-2D mutant is stunted and displays curled leaf morphology. Additionally, it constitutively expresses PATHOGENESIS-RELATED (PR) genes, accumulates salicylic acid, and shows enhanced resistance to the virulent oomycete isolate Hyaloperonospora arabidopsidis (H.a.) Noco2. Subcellular localization assays using GFP fusion constructs indicate that both CHS3 and chs3-2D localize to the nucleus. A third mutant allele, chs3-3D, was identified in an unrelated genetic screen in our lab. This allele contains a C to T point mutation resulting in an M1017 to V1017 substitution in the LRR-LIM linker region. Additionally, a chs3-2D suppressor screen identified two revertant alleles containing secondary mutations that abolish the mutant morphology. Analysis of the locations of these molecular lesions provides support for the hypothesis that the LIM domain represses CHS3 R-like protein activity. This repression may occur through either autoinhibition or binding of a negative defense regulator.